SHAPING STANDARDS: A COMPREHENSIVE ANALYSIS OF CORPORATE GOVERNANCE IN INDONESIAN ISLAMIC BANKS - Ismail, Ahmad Fauzi; Mahamood, Siti Nurhaliza Binti (Research Journal of Economics and Sustainable Development, 2024)
This study aims to examine the effect of ownership structure and corporate governance on the company's liquidity policy. The ownership structure used in this study is managerial ownership and institutional ownership. Meanwhile, the mechanisms of corporate governance used include the size of the board of commissioners, the size of the board of directors, and the size of the audit committee. This study uses the annual reports of Islamic banking companies listed on the Indonesia Stock Exchange (IDX) from 2010-2020. The sampling technique in this study was a purposive sampling method with 55 samples from 5 companies. The data used in this study is secondary data whose data is obtained from the website www.idx.co.id as well as the company's official website. The empirical results of this study indicate that the board of commissioners, audit committee size and institutional ownership are not affecting liquidity policy. While on other variables such as the board of directors, managerial ownership affects liquidity policy.